Nonlinear Control Strategy based on Discrete-Time State Dependent Riccati Equation for Electronic Throttle Control - Lima, Jeferson J. [UNESP]; Santos, Max M. D.; Tusset, Angelo M.; Bassinello, Dailhane G. [UNESP]; Janzen, Frederic C.; Balthazar, Jose M.; IEEE (Ieee, 2016)
This paper aims to present a new control strategy for eletronic throttle control (ETC) used for the acceleration function in a vehicle. Firstly, an analitical model describing is developed with the purpose to evaluation the dynamic behaviour of ETC. The ETC is a non-linear system which the traditional control strategies cannot provide a great control performance. Thus, based on the discret-time state dependent riccati equation (D-SDRE) that has been successfull for the control of non-linear physical plants, we present the application of this control strategy for the ETC. Numerical simulations are done with the purpose to demonstrate a better performance and motivational application of our approach.
Keywords: Electronic Throttle Control; D-SDRE; Nonlinear Dynamic; Optimal Control